PIJAT PERENIUM UNTUK MENCEGAH LASERASI JALAN LAHIR - Astri Yunifitri; Devy Lestari Nurul Aulia; Nova Roza (Universitas Batam, 2022)
Perineal rupture is a condition that is quite common in the normal delivery process. This condition is more at risk for primiparous mothers, big fetus, prolonged labor, delivery with the help of tools such as forceps or vacuum. Postpartum haemorrhage due to perineal rupture is a factor that causes the second highest maternal mortality rate in the world. Perineal massage in the third trimester of pregnancy, can help the perineal muscles become more elastic and strong, thereby reducing the risk of perineal rupture during delivery. The purpose of this literature review is to determine the effectiveness of perineal massage in preventing perineal rupture in pregnant women. The method used is the search method for journal articles in the sciences database from Google Scholar using keywords according to relevant topics and obtained as many as 6 journals that match the inclusion criteria of 10 journal article searches obtained. Based on the results of the study, perineal massage in pregnant women is effective in preventing the incidence of perineal rupture during delivery. Perineal massage performed regularly since gestational age > 34 weeks is effective in reducing the risk of perineal rupture, especially in primiparous women because the perineal and vaginal muscles become more elastic and strong. Regular perineal massage is needed in order to obtain optimal benefits. The role of midwives, husband and family support is very necessary for pregnant women in regularly doing perineal massage.